COVID-19 Pandemic Experiences in Pediatric Intensive Care Unit: An Iranian Referral Hospital-Based Study - Masoud Mohammadpour; Seyed Abbas Hassani; Meisam Sharifzadeh; Leila Tahernia; Setareh Mamishi; Bahareh Yaghmaie; Zeinab Najafi; Farzaneh Beirami; Mehrnoush Afsharipour; Maryam Minuyeefar; Mina Dolatzadeh; Neda Pak; et al. (International Journal of Clinical Practice)
Introduction. In late February 2020, after we had informed about the presence of some cases of COVID-19 in Iran and its rapid spread throughout the country, we decided to make the necessary arrangements for patients with critical conditions in Pediatric Intensive Care Unit (PICU) at Children's Medical Center. There are a little data on critically ill children with COVID-19 infection with ICU requirements. The aim of this study was to describe clinical characteristics, laboratory parameters, treatment, and outcomes of the pediatrics population infected by SARS-CoV-2 admitted to PICU. Materials and Methods. This study was performed between February 2020 and May 2020 in the COVID PICU of the Children’s Medical Center Hospital in Tehran, Iran. Patients were evaluated in terms of demographic categories, primary symptoms and signs at presentation, underlying disease, SARS-CoV-2 RT-PCR test result, laboratory findings at PICU admission, chest X-ray (CXR) and lung CT findings, and treatment. Moreover, the need to noninvasive ventilation (NIV) or mechanical ventilation, the length of hospital stay in the PICU, and outcomes were assessed. Results. In total, 99 patients were admitted to COVID PICU, 42.4% (42 patients) were males, and 66 patients had positive SARS-CoV-2 real-time reverse transcriptase-polymerase chain reaction (RT-PCR). There was no statistically significant difference in the frequency of clinical signs and symptoms (except for fever) among patients with positive SARS-CoV-2 RT-PCR and negative ones. Among all admitted patients, the presence of underlying diseases was noticed in 81 (82%) patients. Of 99 patients, 34 patients were treated with NIV during their admission. Furthermore, 35 patients were intubated and treated with mechanical ventilation. Unfortunately, 11 out of 35 mechanically ventilated patients (31%) passed away. Conclusion. No laboratory and radiological findings in children infected with COVID-19 were diagnostic in cases with COVID-19 admitted to PICU. There are higher risks of severe COVID-19, PICU admission, and mortality in children with comorbidities.